Work Motivation and Human Resources Quality Improvement in PKU Muhammadiyah Sragen in order to Improve Health Services - Rejeki, Mirah; Kusumawardhani, Oktavy Budi (Prosiding University Research Colloquium, 2022)
Human Resources (HR) is very important in institutions such as PKU Muhammadiyah Sragen because it has a role as a driving force for all activities in PKU Muhammadiyah which have quality human resources, it can be easy to realize the vision of the institution by improving the quality of science, skills and provide work motivation to human resources so that they can improve health services for patients. This research was conducted at PKU Muhammadiyah Sragen, Central Java because of the large number of people receiving services, the wide working area of PKU Muhammadiyah Sragen, and a very strategic location near the provincial road. In this research activity using work motivation and improving the quality of human resources as independent variables and health services as the dependent variable. The purpose of this research is to find out how the influence of work motivation and high level of education can improve health services in PKU Muhammadiyah Sragen. This research is a descriptive and causal research. Data analysis used descriptive analysis. The sample technique used is proportional random sampling, based on the results of a questionnaire with 94 respondents from PKU Muhammadiyah Sragen employees, and 90 patients/visitors. The results of this study can be seen that there is a relationship between work motivation, education and improving health services for patients and the community. Conclusion : PKU Muhammadiyah Hospital Sragen health services will increase by increasing work motivation and quality of human resources.